QUALI-QUANTITATIVE ANALYSIS OF THE VEGETATION OF THE “PRAÇA DR. WALDEMAR D’AMBRÓSIO - Nunes Vicente, Lucas; Midori Yada de Almeida, Marcela (Revista Interface Tecnológica, 2020)
Knowing the importance of analyzing the squares and other green areas existing in the urban environment, since this directs actions for the maintenance and conservation of these spaces, this work aimed to analyze qualitatively and quantitatively the vegetation present in Praça do Centenário, in municipality of Taquaritinga-SP. The survey of the existing vegetation in the square was carried out, where the species were identified by the popular name and quantified and, afterwards, it were researched: scientific name, botanical family and origin of the species and tabulated the number of tree individuals, the total number of species, the number of species per family and the number of individuals per family. There were 21 tree species and 10 shrub and herbaceous, distributed in 21 botanical families, in addition to one specie of palm and 13 species of unidentified trees; 124 individuals, 65 trees and 59 palm trees; of this amount, 14 individuals from 13 species of trees and one individual from palm trees were not identified. The species with the largest number of individuals was Syagrus romanzoffiana (jerivá), with 20 specimens, representing 16.1%, of the total of individuals. The Arecaceae family had the highest number of tree species (eight) and the largest number of individuals (59), representing 22.9% of all species and 47.6% of all individuals in this segment, respectively. Considering the species as a whole, 32.3% are native to Brazil, and 67.7% are exotic. Related to shrub and herbaceous species, it were found 10 species, distributed in nine families, with Poaceae being the only one with two representative species.